The Civilising Offensive : Social and educational reform in 19th century Belgium - De Spiegeleer, Christoph; Liberaal Archief (New Perspectives on the History of Liberalism and Freethought, 2018)
"This volume offers a multifaceted selection of studies on 19th-century Belgian reformers and initiatives they instigated to solve the 'social question' by 'civilising' and moralising the lower classes. Around 1850 Belgium was continental Europe's most heavily industrialised state. From the mid-century until the Belle Époque many international social reform associations were based in Belgium, as well as their main international actors. This book aims to place the history of social, moral and educational reform in Belgium during the long 19th century within a broader European perspective. This collection of contributions by both young and established scholars from various disciplinary backgrounds not only fills some gaps in Belgian historiography, but also offers a better understanding of broad epochal processes such as the bourgeois civilising offensive, the expansion of educational action and the historical growth of welfare states.